The subaltern discourse of the Philippine policy on climate change "mimicked without difference"? - Cordovez, Faye Louise H.; Enales, Sharmaine Joy P.; Espada, Jerico O.; Sanglay, Richmond A. (2015)
The aim of this study is to determine the power relations exhibited in the Philippine policy on climate change vis-á-vis the Western modelled frameworks on climate change suggestive on the United Nations Framework Convention on Climate Change (UNFCCC). In light with this, the researchers are interested on identifying the symptomatic claims for a subaltern policy on climate change in the Philippines. Employing Homi Bhabha's